1. Представьте в виде произведения:
![49y^2-y^4=y^2(7^2-y^2)=y^2(7-y)(7+y) 49y^2-y^4=y^2(7^2-y^2)=y^2(7-y)(7+y)](https://tex.z-dn.net/?f=49y%5E2-y%5E4%3Dy%5E2%287%5E2-y%5E2%29%3Dy%5E2%287-y%29%287%2By%29)
2. Разложите на множители:
![8xy+12y-8x-12=\\=8x(y-1)+12(y-1)=\\=(y-1)(8x+12)\\\\b^2+12b+36-25a^2 =\\=(b+6)^2-(5a)^2=\\=\big((b+6)+5a)((b+6)-5a\big)=\\=(b+6+5a)(b+6-5a) 8xy+12y-8x-12=\\=8x(y-1)+12(y-1)=\\=(y-1)(8x+12)\\\\b^2+12b+36-25a^2 =\\=(b+6)^2-(5a)^2=\\=\big((b+6)+5a)((b+6)-5a\big)=\\=(b+6+5a)(b+6-5a)](https://tex.z-dn.net/?f=8xy%2B12y-8x-12%3D%5C%5C%3D8x%28y-1%29%2B12%28y-1%29%3D%5C%5C%3D%28y-1%29%288x%2B12%29%5C%5C%5C%5Cb%5E2%2B12b%2B36-25a%5E2%20%3D%5C%5C%3D%28b%2B6%29%5E2-%285a%29%5E2%3D%5C%5C%3D%5Cbig%28%28b%2B6%29%2B5a%29%28%28b%2B6%29-5a%5Cbig%29%3D%5C%5C%3D%28b%2B6%2B5a%29%28b%2B6-5a%29)
3. Решить уравнение:
х³+6х²+9х = 0
x(х²+6x+9) = 0
x(x+3)²=0
x = 0, x+3 = 0
x = −3
Ответ: x = 0, x = −3.
4. Представить в виде многочлена:
(x−2y)²–(2y–x)(2y+x) =
= x²−4xy+4y²−(4y²−x²) =
= x²−4xy+4y²−4y²+x² =
= 2x²−4xy